Antibiotic resistance genes occurrence and bacterial community composition in the Liuxi River - Xiong, Wenguang; Sun, Yongxue; Ding, Xueyao; Zhang, Yiming; Zeng, Zhenling (Frontiers in Environmental Science, 2014)
Antibiotic resistance genes (ARGs) in the environment have paid great concern due to their health risk. We investigated antibiotics concentrations (tetracyclines, sulfonamides and fluoroquinolones), ARGs abundances (tetracycline, sulfonamide and plasmid-mediated quinolone resistance (PMQR) genes), and bacterial community composition in sediment and water samples in the Liuxi River, China. Antibiotics concentrations were determined by ultra-performance liquid chromatography-electrospray tandem mass spectrometry. ARGs abundances were quantified by a culture-independent method. Bacterial community composition was analyzed by metagenomic approach based on Ion Torrent Personal Genome Machine platform. Antibiotics concentrations were at the levels of 1.19 to 622 ug kg-1 in sediment samples and below the limit of detection to 127 ng L-1 in water samples. Relative abundances (ARGs copies/16S rRNA gene copies) of detected ARGs were at the range of 10-5 to 10-2. The dominant phyla were Proteobacteria, Bacteroidetes and Verrucomicrobia in sediment samples, and were Proteobacteria, Actinobacteria and Bacteroidetes in water samples. The results indicated that the river environment was contaminated by antibiotics and may be as a reservoir of ARGs. This study provided quantitative data on antibiotics, ARGs and bacterial community composition in the Liuxi River, a geographical location different from the reported studies.